GAMBARAN NIAT WANITA USIA SUBUR UNTUK MELAKUKAN DETEKSI DINI KANKER SERVIKS METODE INSPEKSI VISUAL ASAM ASETAT - Novlin Claudi; Sri Utami; Arneliwati Arneliwati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Cervical cancer is a disease that can be prevented through early detection, one of which is the acetic acid visual inspection (IVA) method. IVA is done by applying acetic acid (3-5%) into the cervix which is seen from the color changes that occur. This study aims to describe the intention of WUS to carry out early detection of the IVA method. This research is a quantitative research with descriptive method. The sample used in this study were 34 people with snowball sampling technique. The results of the univariate test showed that the majority of respondents were aged 30-40 years (55.9%), the most education was SMA/equivalent (70.6%) and the majority of the respondents occupations were domestic workers (73.5%). Based on the results of the study, the frequency of intentions in the weak category was 18 people (52.9%), the medium category was 16 people (47.1%) and none was in the strong category. As input for WUS to always increase their activity in participating in programs carried out by the Puskesmas in increasing health-related intentions, especially for cervical cancer.Keywords : cervical cancer; early detection; intention; IVA; WUS